Enhancing Educational Relevance and Graduate Employability through the Penta Helix Collaboration Model: A Strategic Approach for Promoting IAIN Parepare - An Ras Try Astuti; Rezki Fani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
In the context of rapid technological disruption and evolving labor market demands, higher education institutions must ensure that their curricula and programs remain relevant while enhancing graduate employability. This study examines the application of the Penta Helix collaboration model—integrating government, academia, industry, media, and community—as a strategic framework for promoting IAIN Parepare and improving workforce readiness. Employing a sequential exploratory mixed-methods design, qualitative data were collected through interviews, observations, and document analysis, followed by quantitative validation using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings indicate that structured collaboration among Penta Helix stakeholders significantly enhances educational relevance, provides practical learning opportunities, and strengthens alumni competencies, particularly through internships, digital skill development, and adaptive curricula. Government support, industry engagement, and media-driven promotion play pivotal roles in increasing institutional visibility and bridging the gap between academic preparation and labor market requirements. While challenges remain, including uneven stakeholder participation and skill gaps in digital competencies, the study demonstrates that synergistic Penta Helix collaboration fosters graduate employability, institutional branding, and social engagement. The results offer practical implications for Islamic higher education institutions seeking to integrate multi-stakeholder strategies and highlight opportunities for future research on longitudinal impacts and digital innovation in graduate readiness